Life-stage-related desiccation and starvation resistance in the biological control agent Neolema abbreviata - Mulaudzi, Lugisani; Mutamiswa, Reyard; Zachariades, Costas; Chidawanyika, Frank (Wiley, 2022)
Climate variability in the tropics is partly associated with reduced and erratic precipitation, heat waves, and cold snaps thereby exerting abiotic environmental stressors to various arthropod species. For herbivorous insects, such extreme weather events may affect host plant quality and availability resulting in additional stressors such as desiccation and starvation. Neolema abbreviata Larcordaire (Coleoptera: Chrysomelidae) is a key biocontrol agent of Tradescantia fluminensis Vell. (Commelinaceae) and has recently been introduced in South Africa for management of its invasive host plant. However, it remains unknown how environmental stressors may influence its performance under anthropogenic climate change. Here, we investigated the effects of desiccation and starvation on performance of N. abbreviata larvae and adults and implications on biological control. Specifically, we measured desiccation and starvation resistance and critical thermal minima (CTmin) and maxima (CTmax) following stress. Desiccation and starvation pre-treatment reduced both low (CTmin) and high (CTmax) temperature tolerance in both life stages albeit larvae were less cold tolerant and more heat tolerant than adults. In addition, resistance decreased with duration of exposure with desiccation resistance being higher in larvae than adults whereas the converse was true for starvation resistance. This indicates the challenges N. abbreviata may encounter when it faces environmental stressors in nature. Therefore, with projected climate change, this may potentially impact on its field establishment, spread, and effectiveness, thereby negatively influencing future classical biocontrol programs. Overall, the results provide valuable information in modelling potential distribution of N. abbreviata and developing sustainable management options of T. fluminensis under rapidly changing environments.